Ayah "was not" a synthetic study - ليث حازم محمود البّياتي; إبراهيم عبود ياسين السامرائي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
This research is about the verse ((was not)) from Surat Al-Bayeenah, where the meaning of this verse was traced and tackled in terms of linguistic structure and interpretation. The views of scholars on the linguistic structure and interpretation of the verse concerning the original origin of the verse were presented. After the presentation, analysis and discussion of the different views, the study has come up with the following conclusions: • The linguistic structure has a parallel relationship with its semantic meaning. The linguistic structure cannot be detached from its meaning. The context in which the structure is written has a vital impact as it explains the purpose of the structure in that context to reveal the speaker’s attitude. Thus, the linguistic structure cannot be detached from the context in which it is uttered. Consequently, a set of concepts is formed which must be clarified by the researcher that the study of any structure depends on two important elements: the text, and the circumstances surrounding the text in which the structure appears. • The study of the structure is vital for linking the grammatical rules with the interpretative sense of the verse, and thus a precise understanding of the text is extracted through which one can deduce jurisprudential judgments. The understanding of the structure and the parsing reveal the facets of rhetorical inimitability and syntactic aspects found in the Holy Quran. Thus, interpretive meanings are a combination of set of lexemes. This harmony of interrelationship between the words to suggest the meanings which are intended to be delivered to the mind of the recipient is grammar, which, in turn, is the link and the steering to the meanings of the structures in accord with the rules and provisions. • The verb "was" does not indicate in its form past time only when there is evidence; otherwise, it refers to all times past, present and future. • The preposition "even" may come as accusative of the following verbs, and that the preposition (inne ان ) is not the one that performed the accusative form on the following verb, as the word will itself change to “to” which is “even”.